Analisis Performa Bilah Taperless Dengan Airfoil NACA 4412 pada Horizontal Axis Wind Turbine TSD 500 di PT Lentera Bumi Nusantara - Muhammad Alfi Alfaridzi (Universitas Negeri Malang, 2020)
Abstract: The use of wind energy in Indonesia is currently still low due to the average wind speed in the Indonesian territory ranging from 3 m / s to 11 m / s, making it difficult to produce electrical energy on a large scale. However, the potential for wind in Indonesia is available almost all year round, making it possible to develop small-scale power generation systems. Innovations in modifying windmills need to be improved so that in low wind speed conditions it can produce electrical energy. Therefore, a HAWT (Horizontal Axis Wind Turbine) blade design was made using a NACA airfoil which has a high Cl / Cd value and produces 500 W of power at wind speeds of 1 - 11 m / s. The research was conducted in 3 stages. The first calculation phase is to determine the radius, chord and twist of the blade. The two stages of the initial blade design were simulated using QBlade software to determine the NACA airfoil being used and to determine the performance coefficient and the resulting power. The three stages of blade design use Solidworks software which produces a 3D blade design. The design results produce a HAWT blade with a taperless NACA 4412 airfoil with blade radius of 1 m, chord width 0.12 m, and twist angle of 5.08 ° - 12.08 °. At a wind speed of 10 m / s, the blade has a maximum Cp of 52%, a maximum power of 1010 W at an angular speed of 450 rpm, a minimum power of 85 W at an angular speed of 95 rpm. The average power produced is 547.5 W. Field test results of Taperless NACA 4412 blades. The results of the field testing are 585.58 W of maximum charge and an average charge of 30.24 W, with the resulting power of 725.55 Wh. Keywords: Blade, Taperless, NACA 4412,Wind Turbine